Coordinating Cytoskeleton and Molecular Traffic in T Cell Migration, Activation, and Effector Functions - Mastrogiovanni, Marta; Juzans, Marie; Alcover, Andrés; Di Bartolo, Vincenzo (Frontiers in Cell and Developmental Biology, 2020)
Dynamic localization of receptors and signaling molecules at the plasma membrane and within intracellular vesicular compartments is crucial for T lymphocyte sensing environmental cues, triggering membrane receptors, recruiting signaling molecules and fine-tuning of intracellular signals. The orchestrated action of actin and microtubule cytoskeleton, and intracellular vesicle traffic play a key role in all these events that together ensure important steps in T cell physiology. These include extravasation and migration through lymphoid and peripheral tissues, T cell interactions with antigen presenting cells, T cell receptor (TCR) triggering by cognate antigen-MHC complexes, immunological synapse formation, cell activation and effector functions. Cytoskeletal and vesicle traffic dynamics and their interplay are coordinated by a variety of regulatory molecules. Among them, polarity regulators and membrane-cytoskeleton linkers are master controllers of this interplay. Here, we review the various ways the T cell plasma membrane, receptors and their signaling machinery interplay with the actin and microtubule cytoskeleton and with intracellular vesicular compartments. We highlight the importance of this fine-tuned crosstalk in three key stages of T cell biology involving cell polarization: T cell migration in response to chemokines, immunological synapse formation in response to antigen cues and effector functions. Finally, we discuss two examples of perturbation of this interplay in pathological settings, such as HIV-1 infection and mutation of the polarity regulator and tumor suppressor Apc that leads to familial polyposis and colorectal cancer.